Diagnostic significance of hormonal, biochemical and echographic methods in postmenopausal women with endometrial cancer - M. A. Garashova; E. M. Alieva (IRBIS LLC, 2019)
Aim: to evaluate the significance of hormonal, biochemical, and echographic methods in the diagnosis of endometrial cancer.Materials and methods. Fifty patients (aged 62.4 ± 1.0) with endometrial cancer of varying severity and 20 practically healthy postmenopausal women (aged 68.0 ± 0.7) were examined. All patients underwent hormonal, biochemical, and echographic examinations.Results. At the period of this study, 68 % of patients had stage I cancer, 30 % had stage II, and 2 % - stage III endometrial cancer. In the medical history of examined patients, the incidence of abortion was 46.8 %, the rate of childbirth - 70.0 %, the infertility rate - 14.9 % (n = 7). A statistically significant decrease in the luteinizing/follicle-stimulating hormone ratio (0.69 ± 0.09), an increase in the levels of prolactin (467.3 ± 35.1 ng/ml), dehydroepiandrosterone-sulfate (92.9 ± 14.4 pg/ml), estrone (101.60 ± 6.29 ng/ml), progesterone (1.90 ± 0.52 ng/ml), as well as a decrease in estradiol (17.4 ± 3.4 pg/ml) and total testosterone (0.50 ± 0.02 ng/ml) in comparison with the practically healthy postmenopausal women (control group) were found. According to the echographic examination, a pathological increase in the endometrium thickness (24.9 ± 2.7 mm) was detected against the background of uterus and ovaries enlargement. The biochemical parameters in patients with endometrial cancer in the postmenopausal period were within the normal range.Conclusion. The risk of endometrial cancer is high in elderly women with an increased body mass index. Evaluating of their hormone levels is of diagnostic and prognostic importance in endometrial cancer. Transvaginal sonography is an accurate diagnostic method for assessing the tumor invasion into the myometrium of patients with endometrial cancer.